Perception and practice of Kangaroo Mother Care after discharge from hospital in Kumasi, Ghana: A longitudinal study - Nguah Samuel B; Wobil Priscilla NL; Obeng Regina; Yakubu Ayi; Kerber Kate J; Lawn Joy E; Plange-Rhule Gyikua (BMC, 2011)
Abstract Background The practice of Kangaroo Mother Care (KMC) is life saving in babies weighing less than 2000 g. Little is known about mothers' continued unsupervised practice after discharge from hospitals. This study aimed to evaluate its in-hospital and continued practice in the community among mothers of low birth weight (LBW) infants discharged from two hospitals in Kumasi, Ghana. Methods A longitudinal study of 202 mothers and their inpatient LBW neonates was conducted from November 2009 to May 2010. Mothers were interviewed at recruitment to ascertain their knowledge of KMC, and then oriented on its practice. After discharge, the mothers reported at weekly intervals for four follow up visits where data about their perceptions, attitudes and practices of KMC were recorded. A repeated measure logistic regression analysis was done to assess variability in the binary responses at the various reviews visits. Results At recruitment 23 (11.4%, 95%CI: 7.4 to 16.6%) mothers knew about KMC. At discharge 95.5% were willing to continue KMC at home with 93.1% willing to practice at night. 95.5% thought KMC was beneficial to them and 96.0% beneficial to their babies. 98.0% would recommend KMC to other mothers with 71.8% willing to practice KMC outdoors. At first follow up visit 99.5% (181) were still practicing either intermittent or continuous KMC. This proportion did not change significantly over the four weeks (OR: 1.4, 95%CI: 0.6 to 3.3, p-value: 0.333). Over the four weeks, increasingly more mothers practiced KMC at night (OR: 1.7, 95%CI: 1.2 to 2.6, p = 0.005), outside their homes (OR: 2.4, 95%CI: 1.7 to 3.3, p < 0.001) and received spousal help (OR: 1.6, 95%CI: 1.1 to 2.4, p = 0.007). Household chores and potentially negative community perceptions of KMC did not affect its practice with odds of 0.8 (95%CI: 0.5 to 1.2, p = 0.282) and 1.0 (95%CI: 0.6 to 1.7, p = 0.934) respectively. During the follow-up period the neonates gained 23.7 sg (95%CI: 22.6 g to 24.7 g) per day. Conclusion Maternal knowledge of KMC was low at outset. Once initiated mothers continued practicing KMC in hospital and at home with their infants gaining optimal weight. Continued KMC practice was not affected by perceived community attitudes.